Manusia Dalam Perspektif Al-Qur'an, Landasan Kependidikan - Nur Kholis (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Man was created in perfect form. This perfectionincludes spiritual and phsycal aspect to be equipped by its potential. This is in contrast with the view of materialism. Both of these aspect have a functional relationship or monodualism. Developing human potential requires a process of social interaction in internal and formed and surrounding communities which is a process of cultural formation. Culture can be formed throught the instrument of learning, assimilation, adaptation, re-culturalization and reproduction by using symbols. Keywords Human, educational foundation, the perspective of the Koran